2015
DOI: 10.3390/ijerph121114285
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and Other Metals’ Presence in Biomarkers of Cambodians in Arsenic Contaminated Areas

Abstract: Chemical analyses of metal (Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Mo, Ba, and Pb) concentrations in hair, nails, and urine of Cambodians in arsenic-contaminated areas who consumed groundwater daily showed elevated levels in these biomarkers for most metals of toxicological interest. The levels of metals in biomarkers corresponded to their levels in groundwater, especially for As, whose concentrations exceeded the WHO guidelines for drinking water. About 75.6% of hair samples from the population in this study contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Toenail concentration of Mn has been frequently studied both in children [47][48][49][50] and in adults [40], with an LOD ranging from 0.001 [81] to 0.33 µg/g [66] and values usually below 10 µg/g [40]. The highest Mn toenail concentrations have been found in subjects living near a highly industrialized city in Pakistan (average value 52.1 µg/g) [82] and in highly polluted areas in Cambodia (average concentration 43.9 µg/g) [66]. In our study, the average Mn concentration recorded in toenails from exposed children (4.4 µg/g) was slightly higher than that previously reported in pediatric age (3.57 µg/g, weighted means) in an analysis of pooled literature [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toenail concentration of Mn has been frequently studied both in children [47][48][49][50] and in adults [40], with an LOD ranging from 0.001 [81] to 0.33 µg/g [66] and values usually below 10 µg/g [40]. The highest Mn toenail concentrations have been found in subjects living near a highly industrialized city in Pakistan (average value 52.1 µg/g) [82] and in highly polluted areas in Cambodia (average concentration 43.9 µg/g) [66]. In our study, the average Mn concentration recorded in toenails from exposed children (4.4 µg/g) was slightly higher than that previously reported in pediatric age (3.57 µg/g, weighted means) in an analysis of pooled literature [47].…”
Section: Discussionmentioning
confidence: 99%
“…Toenails were selected for sampling as preferential to fingernails due to a minor risk of external contamination [58]. The procedures for toenail collection, sample preparation, and analysis have been extensively employed in previous studies [47,48,[59][60][61][62][63][64][65][66][67].…”
Section: Nail Collection Sample Preparation and Analysismentioning
confidence: 99%
“…Meanwhile, Laohaudomchok et al [50] reported manganese concentration in welders to toenail in the range of 0.05 to 10.41 µg/g, being lower with the finding range of this study. Apart from the fact that the manganese was mostly emitted through welding and various occupational setting, the manganese also can be found in surface soil, groundwater, drinking water, and the accumulation of this metal in terrestrial and aquatic food chain had exposed the elevated of manganese concentration in the human body including in toenail [12], [51], [52]. A chronic effect from a prolonged exposure to manganese toxicity specifically through the industrial common route of exposure (inhalation) may potentially lead to mental disorder and neurotoxicity issues that mainly relates to the damage of central nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…Within the lower Mekong region, notable areas with elevated concentrations of arsenic in groundwater have been reported in Cambodia and Vietnam, while too few data are available to characterize the arsenic situation in Laos and Myanmar [262][263][264][265][266][267]. In Thailand, there is little evidence of naturally occurring arsenic in groundwater, but some areas are impacted by arsenic from mining operations [265].…”
Section: Extent Of the Problemmentioning
confidence: 99%